2012
DOI: 10.1371/journal.pone.0052538
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropism of the Photoperiod-Insensitive Allele of Hd1 on Heading Date, Plant Height and Yield Traits in Rice

Abstract: Five populations segregated in isogenic backgrounds and three sets of near isogenic lines (NILs) overlapping in a 362.3-kb region covering heading date gene Hd1 were developed from the indica rice cross Zhenshan97 (ZS97)/Milyang 46 (MY46). They were used to analyze the effects of Hd1 on heading date, plant height and yield traits. In a background of the parental mixtures, the photoperiod-sensitive allele derived from ZS97 functioned in promoting and delaying flowering in the natural short-day and long-day cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…1). This population has been used to construct NILs for analyzing the effects of Hd1 (Zhang et al, 2012). It was found that the functional Hd1 ZS97 allele was insensitive to photoperiod in the genetic background of ZS97 but promoted heading by 4.64−6.14 days under NSD and NLD conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). This population has been used to construct NILs for analyzing the effects of Hd1 (Zhang et al, 2012). It was found that the functional Hd1 ZS97 allele was insensitive to photoperiod in the genetic background of ZS97 but promoted heading by 4.64−6.14 days under NSD and NLD conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Zhenshan 97 (ZS97) is an early-season rice variety carrying the functional PS allele Se-1 u at the Hd1 locus but has been shown to be photoperiod insensitive (Wei et al, 2012). As compared with Milyang 46 (MY46) carrying photoperiod-insensitive allele Se-1 e , the ZS97 allele promotes heading under both natural short-day (NSD) and natural long-day (NLD) conditions, and meanwhile decreases plant height, spikelet number, grain number and grain yield (Zhang et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that overexpression of OsMYB1R1-VP64 increased grain yield and plant height in rice by delaying flowering time (Figs 1 and 2). Several rice flowering-related pleiotropic genes such as Hd1, Ghd7, DTH8, and DTH7 were discovered in the last 10 years [4,6,7,9]. These genes delay flowering, increase plant height, and increase grain number.…”
Section: Discussionmentioning
confidence: 99%
“…Many pleiotropic genes that function in delayed flowering along with higher yield have been investigated. Those genes have been described as Days to heading 7 (DTH7), Early heading date 2 (Ehd2), Heading date 1 (Hd1), Grain number, plant height and heading date 7 (Ghd7), and Days to heading 8 (DTH8) [4,[6][7][8][9]. Under natural long-day (NLD) conditions, Ghd7 delays flowering by about 20 days and causes yield increases of 50%, and both Hd1 and DTH8 delay flowering time with increasing grain number per spike.…”
mentioning
confidence: 99%
“…Increased expression level of Hd3a and RFT1 reduces number of primary branches per panicle in the line combining Hd1 and Ehd1 [65,66]. In addition, Hd1 increases number of spikelets per panicle and grain yield by suppressing Hd3a expression and delaying heading date [67].…”
Section: Qtls/genes For Rice Yield-related Traitsmentioning
confidence: 96%